Cesare Scurati Sguardi sull'educazione - Calidoni, Paolo; Felini, Damiano; Bobbio, Andrea (Il mestiere della pedagogia, 2021)
On the tenth anniversary from the death of Professor Cesare Scurati, this volume revamps research and reflection on the conceptual, methodological, and operational contribution that this scholar has offered to education at many levels, from childhood to schooling, from life-wide education to the style and ethics of being an intellectual and a teacher. The richness of the pedagogical fresco accomplished by Scurati pertains to the liveliness of a cultural season - the second half of the Twentieth century -, in which educational ideologies and epistemological fences were overcome. Despite all its contradictions and limitations, in this era Scurati achieved productive and humanistic interpretations of education and schooling. In his studies, Scurati effectively tried to improve the situation of several educational ecosystems, intertwining academic reflection and professional training, educational research, analysis of concrete institutional practices, and inspiration from abroad, especially the Anglo-Saxon world. The volume is composed by three sections: the first, Readings, offers some interpretations on the work of Cesare Scurati; the second, Paths, looks deeply on his inquiry on school systems, especially in the curricular perspective and with regards to children education; the third, Environments, gathers contributions on the multiple contexts of the so called life-wide education. The volume, therefore, proposes a non-anecdotal memory of a master, still capable of sparking interests, and promote ideals for the progress of the world.